Limonoids Isolated from Chisocheton pentandrus (Meliaceae) Stembarks and its Cytotoxicity Towards MCF-7 Breast Cancer Cell Line - Runadi, Dudi; Anjari, Intan Hawina; Purnama, Purnama; Nurlelasari, Nurlelasari; Harneti, Desi; Mayanti, Tri; Harizon, Harizon; Hidayat, Ace Tatang; Salam, Supriatno; Azmi, Mohamad Nurul; Supratman, Unang (Makara Journal of Science, 2024)
Chisocheton is a large source of limonoids with various pharmacological effects, such as antiviral, antibacterial, antimalarial, antifungal, and cytotoxic activities. This study aimed to isolate, elucidate, and evaluate the cytotoxicity of limonoids from C. pentandrus stembarks. Isolation was carried out using various separation methods including extraction and column chromatography. Spectral data were analyzed by FT-IR, UV, DEPT 135°, 1H, 13C-NMR, and HRTOF-MS and compared with those previously reported to determine the chemical structure.The obtained limonoids were lasiocarpine (1), lasiocarpine B (2), pentandricine (3), and 16β-hydroxydysobinin (4); all of which were successfully isolated from C. pentandrus for the first time. The cytotoxic activity of these limonoids were also evaluated against Michigan Cancer Foundation-7 (MCF-7) breast cancer cells using PrestoBlue method. Lasiocarpine A revealed the strongest cytotoxicity with an IC50 of 42.62 µM in moderate level.